2001
DOI: 10.1051/0004-6361:20010926
|View full text |Cite
|
Sign up to set email alerts
|

Prominence fine structures in a magnetic equilibrium: Two-dimensional models with multilevel radiative transfer

Abstract: Abstract. In this paper we construct theoretical models for vertical prominence threads which are in magnetohydrostatic (MHS) equilibrium. These models are fully two-dimensional (2D) and take the form of vertically infinite threads hanging in a horizontal magnetic field. A typical example of such a 2D magnetic-dip structure is shown for the case when the central cool parts are surrounded by the prominence-corona transition region (PCTR). We display 2D variations of the pressure, density and temperature. While … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
118
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(126 citation statements)
references
References 8 publications
8
118
0
Order By: Relevance
“…These 2D models were developed by Heinzel & Anzer (2001). These threads are uniform in the vertical direction and the variation in all quantities takes place only in the horizontal plane parallel to the solar surface.…”
Section: Prominence Fine-structure Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…These 2D models were developed by Heinzel & Anzer (2001). These threads are uniform in the vertical direction and the variation in all quantities takes place only in the horizontal plane parallel to the solar surface.…”
Section: Prominence Fine-structure Modelsmentioning
confidence: 99%
“…These threads are uniform in the vertical direction and the variation in all quantities takes place only in the horizontal plane parallel to the solar surface. The 2D threads are in the MHS equilibrium of Kippenhahn-Schlüter type (Kippenhahn & Schlüter 1957) that was generalized to 2D by Heinzel & Anzer (2001) and their temperature structure is specified empirically to encompass both the central cool part and also the prominence-to-corona transition region (PCTR, see Anzer & Heinzel 1999). The PCTR exhibits two distinct forms.…”
Section: Prominence Fine-structure Modelsmentioning
confidence: 99%
“…This was followed by Anzer & Heinzel (1998, 1999, who developed 1D magnetohydrostatic equilibrium models of the Kippenhahn-Schlüter (K-S) type. These were generalized into 2D by Heinzel & Anzer (2001), whose prominence fine-structure models take the form of 2D vertically infinite plasma threads in magnetohydrostatic equilibrium, suspended in magnetic dips. The temperature structure of these prominence fine-structure threads is described semi-empirically and includes the prominence-corona transition region (PCTR).…”
Section: Introductionmentioning
confidence: 99%
“…For intermediate filaments, recent extrapolation models (Aulanier & Démoulin 1998;Mackay & van Ballegooijen 2009;Dudík et al 2008Dudík et al , 2012 have clearly shown that the feet of filaments consist of small threads that are part of long magnetic field lines. These threads are formed by accumulating plasma in dips of the field lines (Heinzel & Anzer 2001;Hillier & van Ballegooijen 2013). In this type of filament, feet are related to parasitic polarities, however they are not rooted in them.…”
Section: Introductionmentioning
confidence: 99%